Characterization of Subsurface Coal Using Seismic Tomography : a Case Study in Muara Enim South Sumatera - Bagus E. B. Nurhandoko; Syahrul Mubarok; Indriani Sukmana; Fajril Ambia; Budi Sulistyanto; Syafrizal Syafrizal; Y. Wiyanto; Hussein Rudiyanto (Indonesian Journal of Physics, 2009)
In recent years, coal as well as coal bed methane becomes important energy resources. Therefore, the characterization of coal seam is also important in predicting the quality, porosity and pore’s fluid of CBM’s reservoir. Seismic wave is very important parameter to characterize reservoir’s properties of coal bed methane as well as quality of coal. In this paper, we show methodology to image the subsurface velocity using seismic tomography. It is very useful for characterizing the coal’s seam as well as to detect the position of intrusion body. A case study was carried out in Suban Block, Muara Enim Sumatera. This coal mining block contains igneous rock intrusion which becoming main control of coal’s quality. Coal which is close with intrusion body usually has better quality than far zone. To acquire the data, we used 48 channels of seismic recorder controlled by telemetry for controlling the shot and first break. Then, data are processed by Fresnel interpolated wave-path (FIW) wide-band inversion tomography. The results show that the intrusion body can be imaged clearly and the seam coal can be delineated from well information. The information in well controls are quite match with tomography results.